2020
DOI: 10.3390/app10010397
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Midsole Bending Stiffness on Lower Extremity Biomechanics during Layup Jumps

Abstract: Purpose: This study aims to investigate the acute effects of shoe midsole stiffness on the joint biomechanics of the lower extremities during specific basketball movements. Methods: Thirty participants wearing stiff midsole shoes (SS) and control shoes (CS) performed layup jumps (LJs) while the kinematics and ground reaction forces were simultaneously collected via the Vicon motion capture system and Kistler force plates. Furthermore, the joint angles, range of motion (ROM), joint power, joint energy, and jump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Through this experiment and combined with previous studies on vertical jumps [ 12 , 22 ], the effect of shoe bending stiffness on the upward jump is concentrated on the MTP joints, and the influence on the hip and knee joints is relatively small.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Through this experiment and combined with previous studies on vertical jumps [ 12 , 22 ], the effect of shoe bending stiffness on the upward jump is concentrated on the MTP joints, and the influence on the hip and knee joints is relatively small.…”
Section: Discussionmentioning
confidence: 77%
“…The authors suggested that the stiffer shoes reduce the energy absorbed from the MTP joint, and the rest of energy would improve about 3.5 cm height (70 kg mass body). Some other studies also found no significant differences between stiff and control conditions in lay-up movement [ 22 ] and running vertical jumps [ 17 ]. One possible reason is that the actual difference in stiffness between the two shoes is too small to generate the significant improvement showed in Stefanyshyn and Nigg's study (energy improvement = mass × height × gravity = 70 × 3.5/100 × 9.81); the experiment of Stefanyshyn and Nigg's [ 12 ] research increased the forefoot stiffness from 0.04 Nm/° to 0.25 Nm/°; our conditions only compared the difference between 0.297 Nm/° and 0.366 Nm/°, so it is not difficult to understand: there are significant differences in MTP joint work, but insufficient changes at the MTP joint to significantly alter athletic performance.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The Vicon 3D analysis system (Vicon Metrics Ltd., Oxford, UK) with eight infrared cameras was utilized to acquire kinematic data of the lower limbs at 200 Hz. Twenty-five reflex markers (9.00 mm in diameter) were used to designate the pelvis, thigh, shank, forefoot, and rearfoot segments ( Figure 1 ) [ 44 ]. Vertical ground reaction forces were measured using AMTI force plates (AMTI, Watertown, MA, USA) at 1000 Hz.…”
Section: Methodsmentioning
confidence: 99%